THE EFFECT OF DURATION OF ACETYLCHOLINE-ESTERASE INHIBITOR ON MMSE, CDT AND BARTHEL INDEX SCORING ON PATIENTS WITH VASCULAR DEMENSIA - Rianawati, Sri Budhi; Damayanti, Ria; Al Rasyid, Harun; Megayasa, Nyoman Artha (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Background: Vascular dementia is a cognitive decline with functional deterioration caused by cerebrovascular disease. It is the second leading cause of dementia. A number of screening questionnaires and models have been developed to help in assessing cognitive function and activity daily living (ADL) in patients with dementia. Mini Mental State Examination (MMSE), Clock Drawing Test (CDT) and Barthel Index are instruments to evaluate cognitive function and ADL of vascular dementia patients. Objective: To determine the role of achetylcholine-esterase inhibitor therapy on cognitive function and ADL in patients with vascular dementia in Saiful Anwar General Hospital.Methods: This study is an analytical study assessing the improvement of cognitive function and ADL of patients with vascular dementia after administration of acethylcholine-esterase inhibitor by assessing the MMSE, CDT and Barthel Index scoring in 1, 3, 6 and 12 month period consecutively.Results: From 15 study subjects, individuals who have been given treatment for 12 months consecutively have the highest increase in MMSE and CDT whilst for Barthel Index has shown highest improvement in one month period.Conclusion: The administration of acetylcholine-esterase inhibitor drugs has the potential to improve and maintain cognitive function and improve ADL. The limited number of study subjects and the many confounding factors that we did not evaluate were the drawbacks of this study. The results of this study cannot be generalized to all patients with vascular dementia and only apply to 15 patients who were the subjects of this study.